One-pot, large-scale green synthesis of silver nanoparticles-chitosan with enhanced antibacterial activity and low cytotoxicity - Jitrada Wongpreecha (2019)
© 2018 Elsevier Ltd Silver nanoparticles stabilized with chitosan (AgNPs-CS) were synthesized based on the one-pot green process in an autoclave, in which CS acts as reducing agent as well as stabilizer. Effects related to temperature and pressure input on particle formation were systematically investigated. Mechanism taking place during particle nucleation and growth was proposed. The data from UV–vis absorption, X-ray diffraction pattern and morphology confirmed the formation of AgNPs-CS with face-centered cubic (fcc) structure. The synthesized AgNPs-CS showed the effective antibacterial activity against both E. coli and S. aureus. The minimum bactericidal concentration values of 39.1 and 312.5 μg/ml for E. coli and S. aureus, respectively, did not show cytotoxicity to L-929 fibroblast. Moreover, the covering of CS on the surface of AgNPs-CS was proven to reduce the cytotoxicity when compared with commercial citrate-stabilized AgNPs. Considering simple and mild process, this synthesis approach would be helpful for development of benign AgNPs-based antibacterial agent.